Sanksi hukum bagi pelaku pelanggaran ubudiyahh - Sofi, Dini Febriana; Hasana, Fajar Wahyu (Maliki Interdisciplinary Journal, 2025)
This research discusses the concept of iqob ubudiyah in the context of religious education at the ma’had, focusing on the violations committed by students and the factors that cause them. Iqob ubudiyah functions not only as a sanction but also as a method for character building and strengthening faith, aimed at disciplining students in performing their religious duties. Through interviews and observations of students from the male and female dormitories, this study found that violations of ubudiyah among male students are more influenced by social and environmental factors, such as busy schedules and peer pressure. Conversely, violations committed by female students tend to be caused by personal reasons, such as lack of discipline and activities outside of prayer times. The results of the study indicate that understanding the factors causing violations of iqob ubudiyah can help in designing more effective development strategies, thereby improving the discipline and morals of students at the ma’had. This research is expected to contribute to the development of a better religious education system.